The Use of Picture Dictionary to Enhance Students’ Vocabulary Mastery at UPTD SMPN 11 Barru - Nurfadhila, A. Putri; Intan, Nur; Asnidar, Anin (IKIP Siliwangi, 2025)
This study examines how effectively junior high school students vocabulary proficiency may be enhanced using pictorial dictionaries. Classroom Action Research was used in this research, and carried out in two cycles with phases for planning, action, observation, and reflection. Twenty-five pupils from SMPN 11 Barru's class VIII.3 took part, and pre- and post-tests were used to gather data. Only 32% of students received the minimum passing score, according to the pre-test data. After implementing picture dictionaries in Cycle I, 40% met the standard, demonstrating initial progress. Cycle II involved refining the teaching approach, leading to a significant improvement, with 100% of students meeting the minimum standard and the average score rising from 66.6 to 80. The findings highlight the potential of picture dictionaries in fostering vocabulary retention and engagement by providing visual and contextualized learning experiences. These results support the integration of picture dictionaries into vocabulary instruction as a practical and effective tool. Future research could explore the use of digital and augmented reality picture dictionaries to enhance learning outcomes further and address limitations related to abstract concepts.